Formononetin Induces Cell Cycle Arrest of Human Breast Cancer Cells via IGF1/PI3K/Akt Pathways In Vitro and In Vivo - Chen, J.; Zeng, J.; Xin, M.; Huang, W.; Chen, X. (Hormone and Metabolic Research, 2011)
Formononetin is one of the main components of red clover plants, and is considered as a typical phytoestrogen. This study further investigated that formononetin inactivated IGF1/IGF1R-PI3K/Akt pathways and decreased cyclin D1 mRNA and protein expression in human breast cancer cells in vitro and in vivo. MCF-7 cells were treated with different concentrations of formononetin. The proliferation of the cells treated with formononetin was tested by MTT assay. The cell cycle in the treated cells was examined by flow cytometry. The levels of p-IGF-1 R, p-Akt, and cyclin D1 protein expression and cyclin D1 mRNA expression in the treated cells were determined by Western blot and RT-PCR, respectively. In addition, the antitumor activity of formononetin was evaluated in nude mice bearing orthotopic tumor implants. Compared with the control, formononetin inhibited the proliferation of MCF-7 cells and effectively induced cell cycle arrest. The levels of p-IGF-1 R, p-Akt, cyclin D1 protein expression, and cyclin D1 mRNA expression were also downregulated. On the other hand, formononetin also prevented the tumor growth of human breast cancer cells in nude mouse xenografts. These results show that formononetin causes cell cycle arrest at the G0/G1 phase by inactivating IGF1/IGF1R-PI3K/Akt pathways and decreasing cyclin D1 mRNA and protein expression, indicating the use of formononetin in the prevention of breast cancer carcinogenesis.
Keywords: formononetin; IGF-1 R; Akt; cyclin D1; breast cancer